The anesthesiologist facing terminality: a survey‐based observational study - Cavalcante, Rodney Segura [UNESP]; Barros, Guilherme Antonio Moreira de [UNESP]; Ganem, Eliana Marisa [UNESP] (Elsevier, 2020)
Background and objectives: Advances in medicine, including anesthesiology and resuscitation, have made natural death increasingly rare. As a consequence, dysthanasia has become usual in a scenario for which there is not rationale. The present study aimed to assess the level of knowledge of Brazilian anesthesiologists on the principles of dysthanasia and orthothanasia. Thence, we studied the management preferences of these professionals, vis‐à‐vis those practices, as well as how medical school contributed to addressing death‐related issues. Method: Quantitative approach, prospective and descriptive cohort that included 150 anesthesiologists, members of the Brazilian Society of Anesthesiology, and who were invited to participate by email. An online questionnaire containing 38 questions was prepared by the authors. The study was approved by the Instructional Research Ethics Committee. Results: Anesthesiologists, although claiming to know dysthanasia and orthothanasia, mostly acquired knowledge outside medical school. If faced with their own end of care, or of a patient or a loved one, they prefer orthothanasia, to die at home, prioritizing dignity. However, the specialists claimed to have already practiced dysthanasia, even when orthothanasia was the choice management, which caused them negative feelings. Almost all respondents stated that they did not have practical training in undergraduate school on how to face end‐of‐life issues, although they felt capable of identifying it. Most were not aware of Federal Council of Medicine Resolution 1.805/06 that makes practicing orthothanasia feasible. Anesthesiologists’ religion or the political‐administrative region of residence had no effect on their preferences. Conclusions: Anesthesiologists claim to have knowledge on dysthanasia and orthothanasia, but prefer, in the face of a terminally ill patient, to practice orthothanasia, although dysthanasia is usual, and results in frustration and indignation. The medical school curriculum is unsatisfactory in addressing death‐related issues.
O anestesiologista frente à terminalidade
Keywords: Anesthesiology; Bioethics; Dysthanasia; Legality (Law)